Variation of mortality after coronary artery bypass surgery in relation to hour, day and month of the procedure - (:unkn) unknown (BMC, 2011)
Background: Mortality and complications after percutaneous coronary intervention is higher when performed after regular duty hours due to challenging patient characteristics, inferior processes of care and limited resources. Since these challenges are also encountered during coronary artery bypass graft (CABG) surgery that is performed after regular work hours, we assessed whether hour and day of procedure influenced mortality after CABG. Methods: We studied 4,714 consecutive patients who underwent CABG at the Minneapolis Veterans Administration (VA) Medical Center between 1987 and 2009. We compared postoperative (30-day) mortality rates in relation to hour and day in which the operation was performed. Results: Operations performed on weekends and after 4 PM had higher risk patients (p < 0.0001) and were more likely to be emergent (p < 0.0001), require intra-aortic balloon pump support (p < 0.0001) and result in postoperative complications (p < 0.0001) compared to those at regular work hours. Mortality was significantly higher when CABG was performed on weekends compared to weekdays (9.4% versus 2.5%; odds ratio (OR) 4.1, 95% confidence interval (CI) 1.6 to 10.4, p = 0.003), and after 4 PM compared to between 7 AM-4 PM (6.2% versus 2.2%; OR 2.9, 95% CI 1 to 8, p = 0.049). In multivariable analysis, when adjusted for the urgency of the operation and the VA estimated mortality risk score, these associations were no longer statistically significant. Conclusions: Mortality after CABG is higher when surgery is performed on the weekends and after 4 PM. These variations in mortality were related to higher patient risk, and urgency of the operation rather than external factors.
Keywords: coronary artery bypass surgery; mortality; ACUTE MYOCARDIAL-INFARCTION; CIRCADIAN VARIATION; SURGICAL OUTCOMES; CARDIAC-SURGERY; IMPROVEMENT; IMPACT; INTERVENTION; FREQUENCY; EFFICACY; STATINS